Isoquercitrin Alleviates Diabetic Nephropathy by Inhibiting STAT3 Phosphorylation and Dimerization - Chen Xuan; Donghui Chen; Shuangna Zhang; Chaofan Li; Qingyun Fang; Dinghua Chen; Jiabao Liu; Xin Jiang; Yingjie Zhang; Wanjun Shen; Guangyan Cai; Xiangmei Chen; et al. (Advanced Science)
Abstract At the convergence point of multiple cytokine signals, signal transducer and activator of transcription 3 (STAT3) is a highly promising therapeutic target for diabetic nephropathy. Isoquercitrin, a natural small‐molecule inhibitor of STAT3, may have beneficial effects on diabetic nephropathy; however, the underlying mechanism remains unclear. Isoquercitrin significantly mitigated renal inflammation and fibrosis by inhibiting STAT3 activity in mice with diabetic nephropathy. Moreover, STAT3 is a direct molecular target of isoquercitrin, which as corroborated by tight and stable noncovalent binding between them. This interaction is mechanistically supported by the affinity of isoquercitrin for the Ser668–Gln635–Gln633 region within the pY+1 binding pocket of the SH2 domain. This binding obstructs pivotal processes like STAT3 phosphorylation and dimerization, thereby suppressing its transcriptional function. Finally, a kidney‐targeted nanocarrier, Iso@PEG‐GK, is developed to load isoquercitrin, thus enhancing its therapeutic precision for diabetic nephropathy. Iso@PEG‐GK significantly improved the absorption and renal distribution of isoquercitrin. This study is the first to demonstrate that isoquercitrin exerts a significant protective effect against diabetic nephropathy and may provide a novel therapeutic drug for this disease.